2021
DOI: 10.1007/s11837-021-04641-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microwave-Assisted Deep Eutectic Solvents to Recycle Lithium Manganese Oxide from Li-Ion Batteries

Abstract: To realize efficient recycling of lithium manganese oxide (LMO) from spent Liion batteries, microwave-assisted deep-eutectic solvent (DES) treatment is proposed. The effects of the DES, temperature, time, and liquid/solid (L/S) ratio on the leaching efficiency were studied by orthogonal and single-factor experiments. The results of the orthogonal experiments indicated that the effects of each factor on the leaching of Li and Mn ions lay in the following order: DES > L/S ratio > temperature > time. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…[18] Additionally, an extraction yield for any target metal (Co, Ni, Mn) higher than 90 % was attained after only 4 h, and a maximum extraction yield close to 100, 93, and 94 % for Co, Ni, and Mn, respectively, was reached after 6 h. To date the highest extraction yield was reported for Co (100 � 3 %) using ethylene glycol:choline chloride (EG:CC) DES, [5,7,8,10,12] almost equal to that obtained using DES formulated using organic acid as hydrogen bond donor. [10,26] To evaluate whether the dissolution of metals was influenced by unknown species contained in the real waste LIBs black mass, a leaching test with duration of 24 h was performed with DESTT by employing commercial NMC111 (LiNi 1/3 Mn 1/3 Co 1/ 3 O 2 ) and NiO. Extraction yields close to those attained with the black mass were found (Figure 1d), excluding that unknown species from the black mass could have influenced metals dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Additionally, an extraction yield for any target metal (Co, Ni, Mn) higher than 90 % was attained after only 4 h, and a maximum extraction yield close to 100, 93, and 94 % for Co, Ni, and Mn, respectively, was reached after 6 h. To date the highest extraction yield was reported for Co (100 � 3 %) using ethylene glycol:choline chloride (EG:CC) DES, [5,7,8,10,12] almost equal to that obtained using DES formulated using organic acid as hydrogen bond donor. [10,26] To evaluate whether the dissolution of metals was influenced by unknown species contained in the real waste LIBs black mass, a leaching test with duration of 24 h was performed with DESTT by employing commercial NMC111 (LiNi 1/3 Mn 1/3 Co 1/ 3 O 2 ) and NiO. Extraction yields close to those attained with the black mass were found (Figure 1d), excluding that unknown species from the black mass could have influenced metals dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, microwave-assisted treatment was employed to enhance the leaching efficiency using choline chloride-oxalic acid (ChCl-OA). [79] The report showed that the leaching efficiencies of both Li and Mn ions reached 99% and 96%, respectively, with only 15 min of microwave heating at 75 C. Although the result , with concentrations of 9.9 Â 10 3 ppm (red line), 7.9 Â 10 3 ppm (dark blue line), 6.6 Â 10 3 ppm (orange line), 4.9 Â 10 3 ppm (yellow line), 3.9 Â 10 3 ppm (light blue line), 3.0 Â 10 3 ppm (dark green line), 2.0 Â 10 3 ppm (gray line), 1.0 Â 103 ppm (light green line), and 0.5 Â 10 3 ppm (purple line). Adapted with permission.…”
Section: Des A)mentioning
confidence: 99%
“…In addition, with the assistance of microwave, the oxaline could efficiently recycle both Li and Mn ions from spent LIBs with a high extraction efficiency of 96% at only 75 °C with a leaching time of 15 min. 212 Additionally, Schiavi et al (2021) 213 focused on improving the selectivity of the DESs-based solvent extraction process towards the target metals (Co, Mn) over the impurities (Fe, Al and Cu). They developed a novel solvometallurgical process containing two successive DES leaching stages conducted at different temperatures (as shown in the flow diagram in Fig.…”
Section: Current Applications Of Des For Metal Recovery and Separatio...mentioning
confidence: 99%
“…35,36 In addition, with the assistance of microwave, the oxaline could efficiently recycle both Li and Mn ions from spent LIBs with a high extraction efficiency of 96% at only 75 °C with a leaching time of 15 min. 212 Furthermore, green leaching processes using DESs were approached to selective extraction of various metal ions from other e-waste, including end-of-life permanent magnets, 130,214 lamp phosphor waste, 215 and printed circuit boards (PCB). 96,118 Specifically, the guanidine hydrochloride-lactic acid (GUC-LAC) combined DES was screened from nine kinds of guanidine-based DESs as the best leachant to selectively extract the rare earth elements, neodymium (Nd), from the end-of-life permanent magnets with a high separation factor (>1300) between Nd and Fe through a simple selective dissolution step followed by precipitation process with oxalic acid.…”
Section: E-wastementioning
confidence: 99%